Conceptual basis for the development of guidance for the use of biomarkers of effect in regulatory risk assessment of chemicals - European Food Safety Authority (EFSA); Antonio Hernández‐Jerez; Susanne Hougaard Bennekou; Laurentius (Ron) Hoogenboom; Henry Mcardle; Christina Pieper; Tanja Schwerdtle; Hendrik Van Loveren; Zainab Al Harraq; Cristina Croera; Anna Christodoulidou; Agnès De Sesmaisons; et al. (EFSA Journal)
Abstract This Scientific Report was carried out in the context of the self‐task mandate (M‐2023‐00097) of the EFSA's Scientific Committee on ‘Guidance on the use of biomarkers of effect in regulatory risk assessment of chemicals’. In the first phase, the project on biomarkers of effect started with a feasibility study (EFSA‐Q‐2024‐00128), with the intention to look closer at definitions and descriptions of biomarkers of effect, as well as to explore several concepts related to the context of application and other scientific principles to be further considered for its development. In addition, relevant activities, initiatives and knowledge in this area were collected and analysed within a complementary mapping study. The outcome of this phase aimed to create a structured basis for future guidance, to identify challenges and to recommend a way forward for its development. The recommendations refer especially to terminologies, the scope of the guidance and several scientific and technical aspects of the selection and interpretation of biomarkers of effect that need to be addressed in future guidance. Moreover, further recommendation refers to the collaborative process to be established with other regulatory organisations that should support the harmonisation and reduce divergencies in the application of methodologies across organisations or sectors.